«Aportar contribución», «experimentar cambios» – Las construcciones con verbo soporte en el español y en el alemán - Rácz, Anita (Acta Hispanica, 2013)
This essay gives an overview about the so called ’light verb constructions’ (LVCs) of the Spanish and German languages. LVCs are formed by the combination of a noun as the semantic, and a verb as the syntactic head of the construction. Since the descprition of their Spanish equivalents has gained attention only recently, we consider it important to adapt and apply the findings of the thorough German experiments on Spanish LVCs.